The application of autologous cancer immunotherapies in the age of memory-NK cells - Lizana-Vasquez, Gaby D.; Torres-Lugo, Madeline; Dixon, R. Brent; Powderly, John D.; Warin, Renaud F. (Frontiers in Immunology, 2023)
Cellular immunotherapy has revolutionized the oncology field, yielding improved results against hematological and solid malignancies. NK cells have become an attractive alternative due to their capacity to activate upon recognition of “stress” or “danger” signals independently of Major Histocompatibility Complex (MHC) engagement, thus making tumor cells a perfect target for NK cell-mediated cancer immunotherapy even as an allogeneic solution. While this allogeneic use is currently favored, the existence of a characterized memory function for NK cells (“memory-like” NK cells) advocates for an autologous approach, that would benefit from the allogeneic setting discoveries, but with added persistence and specificity. Still, both approaches struggle to exert a sustained and high anticancer effect in-vivo due to the immunosuppressive tumor micro-environment and the logistical challenges of cGMP production or clinical deployment . Novel approaches focused on the quality enhancement and the consistent large-scale production of highly activated therapeutic memory-like NK cells have yielded encouraging but still inconclusive results. This review provides an overview of NK biology as it relates to cancer immunotherapy and the challenge presented by solid tumors for therapeutic NKs. After contrasting the autologous and allogeneic NK approaches for solid cancer immunotherapy, this work will present the current scientific focus for the production of highly persistent and cytotoxic memory-like NK cells as well as the current issues with production methods as they apply to stress-sensitive immune cells. In conclusion, autologous NK cells for cancer immunotherapy appears to be a prime alternative for front line therapeutics but to be successful, it will be critical to establish comprehensives structures allowing the production of extremely potent NK cells while constraining costs of production.